Habitabilité et nature urbaines : vers un outil d’évaluation des projets urbains - Muriel Delabarre (Éditions en environnement VertigO, 2012)
The ground of analysis of this article is the metropolis of Lyon and more specifically aquatic urban gardens of The Confluence project. This article concerns the question of urban habitability. We will wonder on the evaluative indicators in urban nature and try to determine an assessment grid of the urban projects. All the complexity of an evaluative approach lies in the criteria of choice of indicators, in particular when the object of study shows itself unstable spatially and temporarily.